Volatility Estimation of Straits Times Index Based on the Anh-Inoue Model - Chatchai Pesee (Agriculture and Natural Resources, 2008)
This paper considers the new dynamic model, namely, the Anh-Inoue dynamic model of complete markets in which the prices of European calls and puts are given by the Black-Scholes formula. The model has memory and can distinguish between historical volatility (HV) and implied volatility (IV). A new method is provided to estimate the implied volatility. It is clear evidence that the historical volatility of Straits Times Index(STI) of Singapore Stock Exchange(SGX) is not constant while the volatility parameter ,σ, of the Black-Scholes model is assumed to be constant throughout the duration in time t. Furthermore, this model can capture some movement of Straits Times Index (STI) of Singapore Stock Exchange(SGX) reasonably well.